Cassava hydrolysates used as substrates for the production of second-generation ethanol by Saccharomyces cerevisiae ATCC 26602 immobilized in sodium alginate spheres (Research, Society and Development, 2024)
Cassava has a prominent position in the Brazilian agriculture and economy. During the production of flour, a very large volume of residue is generated. One way to use these residues is through the production of ethanol. In this context, the present research aimed to use cassava residues as raw material for ethanol production. For this, sulfuric acid was used at concentrations of 1.0 to 5.0% during 5, 10 and 15 minutes of heating in an autoclave. The fermentation was carried out by Saccharomyces cerevisiae ATCC 26602, and to achieve a better performance, it was immobilized in sodium alginate spheres. Ethanol production was also estimated using a synthetic medium added with glucose that served as a comparison standard. The results of the experiment showed that the highest concentration of reducing sugars obtained by the hydrolysis of the residue was with the use of 2.0% of H2SO4 with 15 min. heating at 121 ºC, releasing 56.26 g/L of reducing sugars. The parameters used that led to the highest production of ethanol by the yeast, 7.85 g/L of ethanol, were: pH of 6.5, growth temperature of 30 °C, without agitation. The results showed that cassava residues can be used as a potential substrate for ethanol production. Thus, this work presents data on the most suitable conditions for the use of these industrial wastes in order to generate less polluting fuel energy, an increasingly attractive feature in a world where economic and environmental concerns grow every day.